Peran Orang Tua di kelurahan Tanjung Langkat dalam Membentuk Kepribadian Anak di Era Digital pada Masa Pandemi Covid 19 - Alfian Tanjung; Fenny Mustika Piliang (Medan Resource Center, 2021)
This article aims to discuss the role of parents in the Tanjung Langkat village in shaping children's personalities in the digital era during the Covid-19 pandemic. The way parents educate by giving excessive freedom will have an impact on the lack of intensity of communication between parents and children. This study uses a literature study method, collecting data by identifying discourses from books, papers or articles, journals, newspapers, internet (web), and other information related to the child's personality. Data analysis used descriptive analysis, content analysis, and critical analysis. The negative influence of the digital era has a significant influence on controlling by parents. Family education in the digital era plays a role in directing and guiding their children by setting positive examples to be able to face the challenges of the digital era.